Efficiency improvement of energy storage and release by the inlet position control for seasonal thermal energy storage. (April 2020) - Lim, Hwan Suk; Ok, JungSoo; Park, Jin Soo; Lee, Seung Joo; Karng, Sarng Woo; Kang, Yong Tae
Highlights: A new type of thermal energy storage system with inlet position control method is proposed. The thermal energy storage efficiency could be improved by 24.4% at the end of the third year. The thermal energy sharing ratio by the inlet position control type is improved by 69.4%. The retention time of the fluid is more important than the thermal conductivity of soil during the release period. Abstract: Borehole Thermal Energy Storage (BTES) system is considered one of the most practical technologies in the fields of new regeneration energy or energy conversion. The BTES system can store the solar energy in summer or the waste energy from power plant. It is important to store thermal energy in the BTES system before releasing the energy. Generally, the inlet position for heat source injection is fixed in the BTES system. In this study, the inlet position control method according to the temperature distribution between the borehole and the injected heat source is investigated during the thermal energy storage process. It is confirmed that the energy loss of the conventional type could be minimized and the thermal energy storage efficiency could be improved by controlling the inlet position. Also, the thermal energy release efficiency of the inlet control type is compared with that of the conventional type. The ANSYS/Fluent is used for the simulation analysis of the efficiency improvement by the inlet position control method. The coupled heat transfer calculation between fluid and solid is applied. In the BTES system with the radius of 12.5 m and the depth of 33.5 m, the storage efficiency and thermal energy sharing ratio are improved by 24.4% and 69.4% respectively at the end of the third year during the storage period. And the inlet control type could store the low-grade thermal heat source in the low temperature region of the BTES system, leading to the improvement of the release efficiency by the inlet position control.